Somatostatin Receptor Type 2 Antagonism Improves Glucagon Counterregulation in Biobreeding Diabetic Rats - Karimian, Negar (American Diabetes Association, 2013)
Impaired counterregulation during hypoglycemia in type 1 diabetes (T1D) is partly attributable to inadequate glucagon secretion. Intra-islet somatostatin (SST) suppression of hypoglycemia-stimulated α-cell glucagon release plays an important role. We hypothesized that hypoglycemia can be prevented in autoimmune T1D by SST receptor type 2 (SSTR2) antagonism of α-cells, which relieve SSTR2 inhibition, thereby increasing glucagon secretion. Diabetic biobreeding diabetes-prone (BBDP) rats mimic insulin-dependent human autoimmune T1D, whereas nondiabetic BBDP rats mimic prediabetes. Diabetic and nondiabetic rats underwent a 3-h infusion of vehicle compared with SSTR2 antagonist (SSTR2a) during insulin-induced hypoglycemia clamped at 3 ± 0.5 mmol/L. Diabetic rats treated with SSTR2a needed little or no glucose infusion compared with untreated rats. We attribute this effect to SSTR2a restoration of the attenuated glucagon response. Direct effects of SSTR2a on α-cells was assessed by resecting the pancreas, which was cut into fine slices and subjected to perifusion to monitor glucagon release. SSTR2a treatment enhanced low-glucose–stimulated glucagon and corticosterone secretion to normal levels in diabetic rats. SSTR2a had similar effects in vivo in nondiabetic rats and promoted glucagon secretion from nondiabetic rat and human pancreas slices. We conclude that SST contributes to impaired glucagon responsiveness to hypoglycemia in autoimmune T1D. SSTR2a treatment can fully restore hypoglycemia-stimulated glucagon release sufficient to attain normoglycemia in both diabetic and prediabetic stages.